The remediation of media elements: a case study based on the silver age Batman comics (Revista de Ensino em Artes, Moda e Design, 2023)
Remediation is understood as the process of renewing old content, carried out by new media. The emblematic character of the DC Comics comics (Batman), since its origin in 1939, is considered one of the most well-known and popular, being part of the daily lives of thousands of people in the world and adapting to various media, from analogue to digital over the decades. Therefore, the objective of the present study was to analyze and identify how remediation helped to maintain the status of the Batman character during the Silver Age of comics (1956-1969). For this purpose, a qualitative approach common in, of a basic nature, is used, exploratory studies with bibliographic references related to the topic As a result, it is suggested that remediation stands out as an element of renewal of the medium, as well as helping to popularize a culture of characters.
Keywords: Remediation; Silver Age; Television